The epidemiology of injuries and the first aid knowledge of via ferrata climbers in the European Alps - Thomas Küpper; Travis Heggie; Christian Kühn; Ulrich Schwarz; Volker Schöffl; Audry Morrison; Julia Kühn (University of Applied Sciences in Tarnow, Poland, 2024)
Background: Via ferrata (VF) climbing is an increasingly popular mountain activity in the European Alps. The purpose of this study was to determine the nature of injuries incurred by VF climbers and to understand the extent of their First Aid (FA) knowledge and training. Materials and methods: A questionnaire-based cohort study was performed at two alpine locations. Data included basic data (age, gender, climbing activities, exercise), 18 multiple choice questions with 5 answers each concerning First Aid (FA) knowledge and a self-rating of FA knowledge. Statistics were performed with non-parametric tests. Results: 391 questionnaires were completed. Sunburns (23.9%), contusions (17.7%), open wounds (13.1%), and exhaustion-related injuries were the most reported incidents. Exhaustion was the most common emergency call. Only 52% of climbers wore helmets and gloves, less than 25% had adequate physical conditioning, and 28.1% reported having no FA training. The most common causes of emergencies were weather conditions (19%), stumbles (18.6%), falls (13.4%), and fatigue and deficiency in concentration (13.4%). Only 11 of the surveyed climbers scored 75% on their FA knowledge questions. VF climbers showed significant less FA knowledge than alpine mountaineers. They scored quite high on questions related to general FA but low on questions related to high altitude sickness, back, and thoracic injuries. Conclusions: VF climbers should seek out FA training every two years with an emphasis placed on sunburns, contusions, open wounds, and exhaustion injuries. The training should also emphasize the prevention of back and thoracic trauma and developing rescue strategies.